Atomic structure of ABC rhombohedral stacked trilayer graphene. - Warner, J; Mukai, M; Kirkland, A (2012)
We distinguish between Bernal and rhombohedral stacked trilayer graphene using aberration-corrected high-resolution transmission electron microscopy. By using a monochromator to reduce chromatic aberration effects, angstrom resolution can be achieved at an accelerating voltage of 80 kV, which enables the atomic structure of ABC rhombohedral trilayer graphene to be unambiguously resolved. Our images of ABC rhombohedral trilayer graphene provide a clear signature for its identification. Few-layer graphene interfaces with ABC:BC:BCAB structure have also been studied, and we have determined the stacking sequence of each graphene layer and consequently the 3D structure. These results confirm that CVD-grown few-layer graphene can adopt an ABC rhombohedral stacking.